The Origins of International Investment Law : Empire, Environment and the Safeguarding of Capital / [electronic resource] - Miles, Kate (Cambridge : Cambridge University Press, 2013)
International investment law is a complex and dynamic field. Yet, the implications of its history are under explored. Kate Miles examines the historical evolution of international investment law, assessing its origins in the commercial and political expansionism of dominant states during the seventeenth to early twentieth centuries and the continued resonance of those origins within modern foreign investment protection law. In particular, the exploration of the activities of the Dutch East India Company, Grotius' treatises, and pre-World War II international investment disputes provides insight into current controversies surrounding the interplay of public and private interests, the systemic design of investor-state arbitration, the substantive focus of principles, and the treatment of environmental issues within international investment law. In adopting such an approach, this book provides a fresh conceptual framework through which contemporary issues can be examined and creates new understandings of those controversies.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).